Effect of weeds on the yield of chiltepín pepper - Vera-Mendoza, Carla Alejandra; López-Muraira, Irma Guadalupe; Flores-Martínez, Héctor; Ávila-Miranda, Martín Eduardo; Hernández-Flores, Miguel; Iruegas-Buentello, Héctor Rubén (Revista Mexicana de Ciencias Agrícolas, 2026)
Chiltepín pepper (Capsicum annuum var. glabriusculum) is characterized by being a wild plant appreciated in several regions of Mexico as a condiment and for its intense spiciness. It is a species with small, variable-sized fruits, and as a crop, it can be affected by interference from other undesirable plant species. The research aimed to determine the competitive capacity of weeds on chiltepín fruit yields in terms of weight, number, length, and diameter. A trial was established in 2024 under greenhouse conditions in Tlajomulco de Zúñiga, Jalisco, where the chiltepín pepper crop was maintained with interference from three plant species: Cyperus rotundus (coco-grass), Cynodon nlemfuensis (African bermudagrass), Medicago sativa (cultivated species of alfalfa), emerging weeds and a clean control. The results showed that the treatment with emergent weeds exhibited a total loss of fruit yield (99.97%), followed by C. nlemfuensis, whose greater competitive capacity reduced the yield in weight (88%) and the number of peppers (93%). Treatment with C. rotundus was the one that most affected fruit size, with a 14% reduction in length and a 9.5% reduction in width. Treatment with M. sativa showed interference with fruit weight and number only after the 5th cut, compared with the clean control.